Estudo das propostas de produção textual escrita dos livros didáticos de língua portuguesa do ensino fundamental anos finais de 1960 a 2020 - Lessa Neta, Benigna Soares (2020)
The written text production assignments in Portuguese textbooks have undergone profound terminological, conceptual, structural and methodological changes over time. In view of these changes, this study aimed to investigate the approach to written text production in middle school textbooks in the last seventy years and its correlation with the official educational documents produced throughout that period. Our theoretical background was essentially based on researches that deal with the teaching of written text production, either as a product or as a process, as well as the concepts of language and text in Portuguese textbooks, developed by researchers such as Hayes and Flower (1980), Geraldi (1997), Kato (2001), Reinaldo (2001), Marcuschi (2001), Vieira (2005), Leal (2008), Val (2009), among other authors. Regarding methodological procedures, 14 approaches to written text production found in textbooks before and after the publication of the NCP were analysed, based on two dimensions of analysis: the first, focused on context, took into account: a) the socio-historical aspects of the period in which the approaches to text production were written; b) the linguistic area; c) the prevailing concepts of language and text, and d) the official documents that supply the foundations; the second, more focused on teaching itself, considered: a) the concept of teaching written text production underlying these approaches; b) its themes; c) its motivations, and d) the structure of its statements. The results revealed that the approaches to written text production developed before the publication of the NCP were based on a conception of vertical teaching, through which language was seen either as a code or as a representation of thought, and text production was seen essentially as a product; in the approaches developed during the transition period, we could notice small initial changes in the concepts of teaching written text production; finally, in the approaches elaborated after the publication of the NCP, a time when a concept of language as an instrument of human interaction is in voga, the approaches, in general, are presented from a process perspective, taking into account the stages of planning, development, editing, assessment, rewriting and publication, as well as aspects of their production status: purpose, genre specificity, medium, target audience and readership.